PERSEPSI PARA ORANG TUA TERHADAP PEMBELAJARAN DARING: STUDI PADA SEBUAH SEKOLAH DASAR DI DAERAH PINGGIRAN KLATEN - Bayu Purbha Sakti (Program Studi PGSD Universitas Flores, 2021)
This research is based on the background that online learning is not working effectively because there are some parents who do not have cellphones. Internet signal is also a problem when used in suburban primary schools. The primary school chosen is Public elementary school of Jimbung. The aim is to find out parents' perceptions of online learning. The method of research uses descriptive quantitative survey research. The research subjects used were the parents of fourth grade students because pre-research activities were related to these subjects. Data were collected using a questionnaire instrument with a Likert scale. Data analysis was performed using the Statistical Packages For Social Science (SPSS) program version 20. The result of his research is that parents' perceptions of online learning are determined by attention, experience, barriers, and knowledge. Factors in the category are quite good in terms of factors, namely attention, experience and obstacles. Factors in the good category obtained knowledge factors. The knowledge factor of parents is very supportive of the implementation of online learning. The factors of attention, experience and barriers experienced by parents indicate difficulties in implementing online learning.